Veterinary care of guinea pigs. Part 2: respiratory, cardiac, dental and gastrointestinal disease - Abigail Edis; Sarah Pellett (Companion Animal, 2018)
Guinea pigs are frequently seen in general practice, presented both for routine health checks and for treatment of illnesses. Conditions frequently observed in guinea pigs include respiratory disease, gastrointestinal stasis and dental disease; cardiac disease is also seen. Anorexia must be treated as a matter of urgency. 10.12968/coan.2018.23.12.711